ANALISIS SOSIOLOGI TERHADAP INOVASI TEKNOLOGI - Chairil N. Siregar (Jurnal Sosioteknologi, 2006)
On one hand a technology innovation will increase the social strata of a community, and on the other hand, it causes some social conflicts though they can be controlled. Furthermore, the speed of a technology innovation will affect a society to which it is introduced. One of the effects is that the society experiences a cultural lag. Therefore, it is necessary that the engineers take into account the social aspects into their technology innovation. This tradition "“ in which science and sociology are combined "“ has existed since hundreds of years ago. This combination results from the fact that during the innovation process, some engineering and scientific problems cannot be separated from the economic, social, political, and cultural problems of a society.